Photodynamic therapy treats acne by altering the composition of the skin microbiota. Issue 1 (29th December 2022) - Guo, Yangmin; Zeng, Mi; Yuan, Yumeng; Yuan, Mengsi; Chen, Yanxia; Yu, Haoyang; Liu, Ruimin; Ruan, Zhijie; Xie, Qingdong; Jiao, Xiaoyang; Lu, Tao
Abstract: Background: Acne is the eighth‐most prevalent inflammatory skin disease with no optimal treatment. Photodynamic therapy (PDT) is an effective treatment for severe acne. Aims: The effect of PDT on the composition and diversity of skin microflora in severe acne patients was studied. Materials and Methods: A total of 18 patients with severe acne and 8 healthy individuals were selected for this study. Patients were treated with 5‐aminolevulinic acid‐mediated PDT once a week three times in total; the skin microbiome was measured by 16S ribosomal RNA gene sequencing before and after treatment (1 week after each PDT). Results: The microflora composition was different between healthy controls and patients, and between patients before and after treatment. Alpha diversity indices were lower in patients than those in control. There were 15 bacterial genera with high relative abundance that had noticeable changes during treatment. At the genus level, particularly Cutibacterium acnes ( C. acnes formerly Propionibacterium acnes ), there was no statistically significant difference among different group. The abundances of Staphylococcus epidermidis and Staphylococcus aureus were low. Discussion: The microbial composition is different between severe acne patients acne patients and healthy individuals. The therapeutic efficacy of severe acne treated with PDT is associated with the composition and diversity of skin microbiota. Conclusion: The skin microbial composition changes after PDT treatment. PDT is an effective method for the treatment of severe acne.